Analisis Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan PT XYZ - Salsabilla Anjani Putri; Bangun Putra Prasetya (Universitas 45 Surabaya, 2024)
This study aimed to analyze the effect of compensation and work environment on employee job satisfaction at PT XYZ. The research employed a qualitative method with primary data collected through interviews with nine employees, and secondary data obtained from books and other relevant sources. The interviews revealed that PT XYZ provided compensation based on employee performance, using a daily wage system and providing allowances. However, some employees expressed dissatisfaction with the given salary and allowances. Meanwhile, the work environment was considered supportive, with employees assisting each other and supervisors conducting oversight. The study concluded that PT XYZ needs to improve its compensation policy and provide a better work environment to enhance employee job satisfaction. Further research with a broader scope is recommended to gain more comprehensive insights.